Comparative advantage and competitiveness of COVID-19-related medical products exporters - Idris, Zera Zuryana; Ismail, Normaz Wana; Ibrahim, Saifuzzaman (Tomas Bata University, Zlin, 2022)
The coronavirus disease (COVID-19) pandemic generated an upsurge in demand for medical products. Trade policy changes, including export restrictions and import reforms, have led to a shortage of medical products. The World Health Organization has recommended countries to encourage local production and identify various import sources for medical products to ensure sustainable healthcare capacity to combat the COVID-19 pandemic and any similar events in the future. This study aims to examine the comparative advantages and competitiveness in producing medical products among top exporters. The contribution of this study is the ability to identify various import sources specific to developing countries. From the exporter’s perspective, this study allows countries to recognize their existing competitive strengths in the medical products trade, allowing them to strategize and compete in the international markets of medical products. Using Balassa’s revealed comparative advantage index, this study analyzes 25 primary medical product exporters, identifying several countries with a comparative advantage in producing medical products. Medicines are primarily dominated by high-income countries, including Switzerland and Germany, whereas middle-income countries, such as China and Malaysia, are more specialized in medical supplies, medical equipment, and personal protective products. This finding provides a basis for policy formulation that can facilitate the process of building a sustainable healthcare capacity.